Does Forum Theater Help Reduce Gender Inequalities and Violence? Findings From Nepal - Dahal, Pranab (Journal of interpersonal violence, 2022)
Gender inequality and violence against women are present in every society and culture around the world. The intensities vary, however, based on the local guiding norms and established belief systems. The society of Nepal is centered on traditional belief systems of gender roles and responsibilities, providing greater male supremacy and subordination for the females. This has led to the development and extensive practices of social gender hierarchal systems, producing several inequalities and violence toward women. This study has utilized Forum Theater interventions as a method of raising awareness in 10 villages in eastern Nepal. The study aimed to understand the perception and changes in the community and individuals from the interactive Forum Theater performances on pertinent local gender issues. We conducted 6 focus group discussions and 30 individual interviews with male and female participants exposed to the interventions. The data analysis utilized the constructivist grounded theory methodology. The study finds that exposure and interactive participation in the Forum Theater provide the audience with knowledge, develop empathy toward the victim, and motivate them to change the situation of inequality, abuse, and violence using dialogues and negotiations. The study describes how participation in Forum Theater has increased individual?s ability for negotiating changes. The engagement by the audience in community discussions and replication of efforts in one of the intervention sites show the level of preparedness and ownership among the targeted communities. The study shows the methodological aspects of the planning and performance of the Forum Theater and recommends further exploration of the use of Forum Theater in raising awareness.